Tubular Surfaces with Galilean Darboux Frame in G3 - Yoon, Dae Won; Yuzbasi, Zuhal Kucukarslan (B Verkin Inst Low Temperature Physics & Engineering, 2019)
The main point of the research is to study a new approach for defining the tubular surfaces with the Galilean Darboux frame in 3-dimensional Galilean space. Also, we obtain the Gaussian and mean curvatures and derive some parametrizations for a special curve to lie on tubular surfaces with the Galilean Darboux frame.
Keywords: tubular surface; Galilean Darboux frame; geodesic; asymptotic; Galilean space